2021
DOI: 10.1002/ece3.7312
|View full text |Cite
|
Sign up to set email alerts
|

Highly variable chloroplast genome from two endangered Papaveraceae lithophytes Corydalis tomentella and Corydalis saxicola

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 67 publications
(88 reference statements)
4
23
0
Order By: Relevance
“…Mononucleotide SSRs which exist in a large numbers in cp genomes (George et al., 2015 ; Liang et al., 2019 ) are the most abundant (Table 3 ), and A/T motifs are the most common (Figure 3 ; Appendix Table S9 ). This finding is similar to previously reported patterns of land plants (George et al., 2015 ; Huang et al., 2021 ; Ren et al., 2021 ; Vieira et al., 2014 ; Wei et al., 2021 ). However, in Polypodiaceae plastomes, most repeats were C/G mononucleotides.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Mononucleotide SSRs which exist in a large numbers in cp genomes (George et al., 2015 ; Liang et al., 2019 ) are the most abundant (Table 3 ), and A/T motifs are the most common (Figure 3 ; Appendix Table S9 ). This finding is similar to previously reported patterns of land plants (George et al., 2015 ; Huang et al., 2021 ; Ren et al., 2021 ; Vieira et al., 2014 ; Wei et al., 2021 ). However, in Polypodiaceae plastomes, most repeats were C/G mononucleotides.…”
Section: Discussionsupporting
confidence: 92%
“…The distribution of SSRs in some chloroplast (cp) genomes is nonrandom and dominated by mononucleotides, where A/T bases account for the majority (Ellegren, 2004 ; George et al., 2015 ; Ren et al., 2021 ). Some Polypodiaceae species show similar SSR distribution patterns in their cp genomes (Liu et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported a marked IR region expansion in some Corydalis cp-genomes; the IR region expanded into the simple sequence repeat (SSR) region and led to IR–SSC boundary variations 1 , 2 . In the present study, three newly sequenced Corydalis cp-genomes were compared with the C. edulis cp-genome, which exhibited a typical angiosperm quadripartite cp-genome structure (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, deep relationships remained poorly resolved by this phylogenetic approach applying a few plastid markers. Some studies reported that the protein-coding genes shared by all taxa could be used to reconstruct a phylogeny 2 , 34 . However, single-copy genes (SCGs) have subsequently emerged as candidates for phylogenetic analysis because paralogues are derived from duplication events other than speciation events and should therefore be discarded from phylogenetic analyses 69 , 70 .…”
Section: Discussionmentioning
confidence: 99%
“…Chloroplasts genomes regarding gene content and order are highly conserved, with the potential for the understanding of the taxonomy, phylogeny and evolution of plants (Ahlert et al 2003 ; Moore et al 2010 ). But less than ten species of Corydalis genomes are publicly available in NCBI to data (Wu et al 2020 ; Xu and Wang 2020 , 2021 ; Liu et al 2021 ; Ren et al 2021 ). Corydalis fangshanensis W.T.…”
mentioning
confidence: 99%